First report of fababean (Vicia faba L.) rust caused by Uromyces vicea-faba in North East India - Rajesha, G; Bendangsenla; Kumar, Rakesh (Indian Journal of Plant Protection, 2023)
The occurrence of rust disease caused by Uromyces vicea faba on faba bean was observed during January-February of 2016 and 2017 in ICAR Research Farm, Dimapur district of Nagaland. The rust pustules were initially light brown colour which later turns into dark brown. After aging, rust pustules become corky encrustation on leaves. Under microscope, the rust spores were observed and confirmed with the presence of uredospores and teliospores. Uredia are yellowish- brown colour, round with double layers. Whereas the telia were elongated dark brown in colour with elongated stalk. It is a first report of rust disease on faba bean in North-East India.